The political economy of public research investment and commodity policies in agriculture: an empirical study. - Swinnen, J.F.M.; de Gorter, H.; Rausser, G.C.; Banerjee, A.N. (Agricultural Economics, 2000)
The paper tests a political economy theory of simultaneous government decision-making on income redistribution through commodity policies and on public research investment in agriculture. We use data from 37 countries on agricultural protection and public agricultural research expenditures (PARI). The empirical results are consistent with the political economy hypotheses. The analysis suggest that structural changes in the economy have important effects on the political incentives for governments not only to subsidize or tax farmers, but also to invest in public agricultural research. Furthermore, the analysis supports the hypotheses that the impact of such structural changes on government decision-making on PARI is non-linear and conditional on other factors. Regarding the impact of political institutions, the results suggest that more democracy neither leads to more distortionary transfers (agricultural protection), nor to lower investment in public goods (PARI).
Keywords: Agricultural protection; Public research investment; Political economy.